Aortic root surgery in Marfan syndrome: comparison of aortic valve-sparing reimplantation versus composite grafting - Karck, Matthias; Kallenbach, Klaus; Hagl, Christian Matthias; Aichele, Christine; Leyh, Rainer Günther; Haverich, Axel (The journal of thoracic and cardiovascular surgery, 2004)
Objective - The objective of this study was to compare the results of aortic valve-sparing reimplantation and aortic root replacement with mechanical valve conduits in patients with Marfan syndrome undergoing operation for aortic root aneurysms. - Patients and methods - Between March 1979 and April 2002, 119 patients with clinical evidence of Marfan syndrome underwent composite graft replacement with mechanical valve conduits (n = 74) or aortic valve-sparing reimplantation according to David (n = 45). The underlying causes were aortic dissection type A (43 patients) and aneurysms (76 patients). - Results - Patients undergoing aortic valve reimplantation were younger compared with patients undergoing composite grafting (28 vs 35 years, P = .002) and had longer intraoperative aortic crossclamp times (125 vs 78 minutes, P < .0001) and extracorporeal circulation times (162 vs 124 minutes, P < .0001). Early postoperative mortality was 6.8% (n = 5) in patients undergoing composite grafting and 0% in patients undergoing aortic valve reimplantation (P = .15). Mean follow-up was 30 months for patients undergoing aortic valve reimplantation and 114 months for patients undergoing composite grafting. Freedom from reoperation and death after 5 years postoperatively was 92% and 89% in patients undergoing composite grafting and 84% and 96% in patients undergoing aortic valve reimplantation (P = .31; P = .54), respectively. Thromboembolic complications or late postoperative bleeding occurred in 17 patients undergoing composite grafting, and an early postoperative event occurred in 1 patient undergoing aortic valve reimplantation. - Conclusions - The results of aortic valve reimplantation and composite grafting of the aortic valve and ascending aorta with mechanical valve conduits are similar with regard to early and mid-term postoperative mortality and to the incidence of late reoperations in patients with Marfan syndrome. The low risk of thromboembolic or bleeding complications favors aortic valve reimplantation in these patients.